Effects of timber harvest on structural diversity and species composition in hardwood forests - FARZAM TAVANKAR; AMIR ESLAM BONYAD (Biodiversitas Journal of Biological Diversity, 2015)
Tavankar F, Bonyad AE. 2015. Effects of timber harvest on structural diversity and species composition in hardwood forests. Biodiversitas 16: 1-9. Forest management leads to changes in structure and species composition of stands. In this research vertical and horizontal structure and species composition were compared in two harvested and protected stands in the Caspian forest of Iran. The results indicated the tree and seedling density, total basal area and stand volume was significantly (P < 0.01) higher in the protected stand. The Fagus orientalis L. had the most density and basal area in the both stands. Species importance value (SIV) of FagusÂ orientalis in the protected stand (92.5) was higher than in the harvested stand (88.5). While, the SIV of shade-intolerant tree species such as Acer insigne, Acer cappadocicum and Alnus subcordata was higher in the harvested stand. The density of trees and seedling of raretree species, such as Ulmus glabra, Tilia begonifolia, Zelkova carpinifolia and Fraxinus coriarifolia, was also higher in the protected Â stand. The Shannon-Wiener diversity index in the protected stand (0.84) was significantly higher (P < 0.01) than in the harvested stand (0.72). The highest diversity value in the harvested stand was observed in DBH of 10-40 cm class, while DBH of 40-70 cm had the highest diversity value in the protected stand.